Effects of Standard and Half-Kneeling Cardiopulmonary Resuscitation - Uhm, Tai-Hwan; Kim, Jee-Hee; Kim, Jin-Hwa (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this paper is to suggest a position that complies with recent basic CPR guidelines emphasizing chest compression through comparison between standard cardiopulmonary resuscitation (CPR) and half-kneeling CPR.Methods/Statistical analysis: Sixteen participants performed 30:2 conventional CPR and compression-only CPR in standard, kneeling on both side positions, and 30:2 conventional CPR and compression-only CPR in half-kneeling position, respectively four times each. 30:2 conventional CPR was performed 10 cycles and compression-only CPR was performed with 300 chest compressions. A short print out from the mannequin of four types of CPR were compared with one-way ANOVA. Independent sample t-test and two-way ANOVA was performed.Findings: There was no statistically significant difference between standard CPR and half-kneeling CPR. However, incorrect pressure point and incomplete recoil were found in half-kneeling compression-only CPR. Half-kneeling compression-only CPR of the heavy group and small group showed incorrect pressure point and incomplete recoil.Improvements/Applications: In half-kneeling compression-only CPR, there were incorrect pressure points and incomplete recoil when weights were heavier or smaller. In half-kneeling CPR training, chest pressure point and recoil must be mastered further.